Representasi Identitas Muslimah Modern â€œJilbab Travelerâ€ dalam Novel Karya Asma Nadia - Putri, Rani Dwi (JSW (Jurnal Sosiologi Walisongo), 2020)
Following the fall of the New Order era, which encouraged media development and openness, Islam was positioned as a dominant identity in public spaces. Asma Nadia is one of the actors who is become one part of those phenomena. Her works in novels, films and soap operas have succeeded in combining modern elements with Islamic symbols and values. The theme of Jilbab traveler is one example. Applying text analysis focusing on three works of Asma Nadiaâ€™s novels, namely The Jilbab Traveler; Assalamualaikum Beijing; Jilbab Traveler: Love Sparks in Korea, this article reveals that Asma Nadia illustrates "jilbab traveler" as both agile and pious. The ambition to travel around the world accompanied by its inherent attributes represents the figure of â€œjilbab travelerâ€ as an agile woman, while hijab (veil) presents an image of a pious woman. On the other side, the wearing of the veil becomes a distinction and provides such negotiation space and illustrates the hegemonic masculinity of patriarchal culture.